Thermodynamics of a Multicomponent Gaseous Phase as Viewed by the Balance Theory - Wrzesiński, Z. (Engineering Transactions, 2002)
The article presents some formalised definitions of volume density of the molar number of a mixture and a mixture component. With the help of the above definitions, the molar concentration of a mixture component has been determined. An analysis has also been made to define partial volume density. The mass density of a substance component production has been defined and the notion of the referential density of the stream exchange of a substance component has been applied to analyse the movement of substance components in the mixture, whereby defining the notion of a diffusion stream density. Next, with the help of the referential balance equation of a substance component, an analysis has been made of the balance of substance components leading to the definition of an equation of diffusion continuity which in turn, under the accepted constraints, leads to the so-called second Fick's law.